2018
DOI: 10.1093/aje/kwy209
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Diffusion of the 1918 Influenza Pandemic in British India

Abstract: The factors that drive spatial heterogeneity and diffusion of pandemic influenza remain debated. We characterized the spatiotemporal mortality patterns of the 1918 influenza pandemic in British India and studied the role of demographic factors, environmental variables, and mobility processes on the observed patterns of spread. Fever-related and all-cause excess mortality data across 206 districts in India from January 1916 to December 1920 were analyzed while controlling for variation in seasonality particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
(75 reference statements)
0
18
1
Order By: Relevance
“…When estimated at the mid-point of Barro et al's and Davis's estimates (reported in the table), British India accounted for 45 per cent of total global pandemic deaths 13 . There were notable spatial differences in deaths in the subcontinent, with western, northwestern, and central regions recording much higher mortality rates (Reyes et al 2018;Chandra and Kassens-Noor 2014;Mills 1986;Gill 1928). The relative importance of differences in diurnal temperature, comorbidity, food scarcity, and other related factors that determined people's susceptibility to the virus remains an unresolved issue.…”
Section: Geographical Patternsmentioning
confidence: 99%
“…When estimated at the mid-point of Barro et al's and Davis's estimates (reported in the table), British India accounted for 45 per cent of total global pandemic deaths 13 . There were notable spatial differences in deaths in the subcontinent, with western, northwestern, and central regions recording much higher mortality rates (Reyes et al 2018;Chandra and Kassens-Noor 2014;Mills 1986;Gill 1928). The relative importance of differences in diurnal temperature, comorbidity, food scarcity, and other related factors that determined people's susceptibility to the virus remains an unresolved issue.…”
Section: Geographical Patternsmentioning
confidence: 99%
“…Active research topics in the field of archeo-epidemiology include the search for predictors of influenza mortality, such as socioeconomic indicators or geography, and the drivers of influenza spatial diffusion. In 2 articles in the present issue, the authors concentrated on the spatial diffusion of influenza, focusing on British India and Portugal, 2 countries that have been poorly studied in the context of the 1918 pandemic ( 10 , 11 ). Both studies revealed a highly heterogeneous spread of the pandemic and geographic variation in pandemic mortality impact, albeit at different spatial scales.…”
Section: Influenza Mortality Burden Risk Factors and Spatial Spreadmentioning
confidence: 99%
“…Although Portugal as a whole was severely hit by the pandemic compared with other European countries, some provinces nearly fully escaped ( 10 ). Analysis of district-level mortality records in India revealed a northeastward wave of infection from September to November 1918 that was associated with climate and population density ( 11 ). Diffusion was driven by long-distance jumps via the railroad network, superimposed on local diffusion between neighboring provinces.…”
Section: Influenza Mortality Burden Risk Factors and Spatial Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of spatial manifestation of the demographic phenomena, such as mortality, enables a better understanding of the spread of the Spanish flu, as well as other infectious diseases throughout history. It can also be applied in modern spatial demography and spatial epidemiology for designing more efficient public health interventions for future outbreaks with similar characteristics (Chowell, Bettencourt, Johnson, Alonso, & Viboud, 2007) and for developing public health countermeasures and implement effective mitigation plans (Reyes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%